Factors related to cardiac rupture after acute myocardial infarction - Gao, Xue; Guo, Ying; Zhu, Xiaoting; Du, Chunlei; Ma, Beibei; Cui, Yinghua; Wang, Shuai (Frontiers in Cardiovascular Medicine, 2024)
Background Cardiac rupture (CR) after acute myocardial infarction (AMI) is a fatal mechanical complication. The early identification of factors related to CR in high-risk cases may reduce mortality. The purpose of our study was to discover relevant risk factors for CR after AMI and in-hospital mortality from CR. Methods In this study, we enrolled 1,699 AMI cases from October 2013 to May 2020. A total of 51 cases were diagnosed with CR. Clinical diagnostic information was recorded and analyzed retrospectively. We randomly matched these cases with AMI patients without CR in a 1:4 ratio. Univariate and multivariate logistic regression and stratifying analysis were used to identify risk factors for CR. Univariate and multivariate Cox regression hazard analysis and stratifying analysis were used to assess predictors of in-hospital mortality from CR. Results The incidence of CR after AMI was 3.0% and in-hospital mortality was approximately 57%. Multivariate logistic regression analysis identified that white blood cell count, neutrophil percentage, anterior myocardial infarction, a Killip class of >II, and albumin level were independently associated with CR (p < 0.05). Stratifying analysis showed that age, systolic blood pressure, and bicarbonate were independent risk factors for female CR (p < 0.05) but not male CR. Triglyceride and cardiac troponin I were independent risk factors for male CR (p < 0.05) but not female CR. Anterior myocardial infarction, a Killip class of >II, and neutrophil percentage were independent risk factors for male and female CR (p < 0.05). Multivariate Cox regression analysis showed that the time from symptom to CR and the site of CR were independent predictors for in-hospital mortality from CR (p < 0.05). Stratification analysis indicated that risk factors did not differ based on gender, but platelet counts were predictors for in-hospital mortality in female and male CR. Conclusion Low albumin, a high white blood cell count, neutrophil percentage, anterior myocardial infarction, and a Killip class of >II were independent and significant predictors for CR. However, risk factors are different in male and female CR. The time from symptom to CR, the site of CR, and platelet counts were independent predictors for in-hospital mortality from CR. These may be helpful in the early and accurate identification of high-risk patients with CR and the assessment of prognosis. In addition, gender differences should be considered.